BIMBINGAN KONSELING LINTAS AGAMA DAN BUDAYA DALAM PENANGGULANGAN RADIKALISME AGAMA BAGI REMAJA - Hamzan wadi (Al-Tazkiah : Jurnal Bimbingan dan Konseling Islam, 2020)
The country of Indonesia is a multicultural country with diverse tribes, cultures, religions and understandings which have the opportunity to open opportunities for various understandings to influence it. In the world of education, it is one of the targets for spreading the seeds of potential religious radicalism. Understanding religious radicalism tends to ignore aspects of diversity and negate diversity. The psychological state of adolescents is a period that is vulnerable and sensitive to environmental influences. At this time, adolescents are synonymous with a period of self-discovery and a desire to strengthen the search for their identity. Cross-Religion and Culture counseling services are one of the services in the world of education that is very strategic in overcoming the spread of religious radicalism among adolescents. Counseling services through a multicultural concept are considered very necessary in shaping the personalities of adolescents who are able to respect each other in any diversity of diversity. From this study intends to show that multicultural counseling is one way to foster the civilized attitude of students so that they are not trapped in the wrong understanding of the differences they have.